Influencing health policy through public deliberation: Lessons learned from two decades of Citizens'/community juries. (April 2017) - Degeling, Chris; Rychetnik, Lucie; Street, Jackie; Thomas, Rae; Carter, Stacy M.
Abstract: Citizens'/community juries [CJs] engage members of the public in policy decision-making processes. CJs can be employed to develop policy responses to health problems that require the consideration of both community values and scientific evidence. Based on the principles of deliberative democracy, recent reviews indicate that findings from CJs have successfully been used to influence health policy decision-making. Despite this evidence of success, there appears to be a gap between the goals of health researchers who organize CJs and the needs of policy actors and decision makers. Drawing on our experiences working with CJs and recent research on CJ methods, we describe a synopsis of the current state of the art organized around four key questions, and informed by insights from deliberative theory and critical policy studies. Our intention is to stimulate further discussion as to the types of health policy questions that can be usefully addressed through public deliberation, and provide guidance on the methodological and political dimensions that need to be considered in deciding whether a CJ is an appropriate approach for informing a policy decision-making process. Highlights: Community juries (CJs) elicit public deliberation to inform policy decisions. We discuss how to make CJs policy-relevant, organized around four key issues. These are: audience, policy influence-point, research question, and juror selection. Greater methodological integrity in CJ research will increase legitimacy of findings.